Evaluation of the criteria for diagnosis of pulp and periapical diseases performed by dentists in primary care in the Municipality of Arcoverde/PE (Research, Society and Development, 2021)
Correct diagnosis is the key point in the treatment of any disease, avoiding unforeseen events, complications, and injuries. In Endodontics, the diagnosis of pulp and periapical pathologies is carried out with basic dental care provided by the Brazilian public health service. Aiming at improving the oral health service, this study aimed to evaluate the conduct of dental surgeons in the municipality of ArcoverdePE in the diagnosis of pulpal and periapical changes. A quantitative-descriptive study was carried out by means of an online questionnaire applied to the professionals of the Unidades Básicas de Saúde (Basic Health Units). After organization and categorization, the results revealed that most professionals have a postgraduate degree (88.9%), are permanent employees (77.8%), and have less than 3 years of experience in primary care in the municipality of Arcoverde (66.66%). There is a high frequency of diagnosis of pulp and periapical alterations in UBSFs (39.74%). Professionals considered themselves capable of recognizing more clinical aspects of pulpal and periapical diseases (85.47%) and endodontic diagnosis (61.11%). Only 36.56% were the mean value of correct answers for the identification of clinical features, 35.07% for radiographic aspects and 35.69% of the answers to the semiotechnical tests. According to the methodology employed, it can be concluded that most dentists in primary care in the municipality of Arcoverde/PE have insufficient knowledge and poorly use the criteria for diagnosis of pulp and periapical diseases.